Design and Development of ARM based Electronic Test Evaluation System for RTO - Shweta Salokhe; U. L. Bombale (Institute of Advanced Engineering and Science, 2016)
Electronic test evaluation system for driving license is very useful now a days, as there is increase in the human intervention in the system. This system make the driving license procedure transparent to human being. The proposed technological solution is advancement towards the automation of system and improves the driving test accuracy. As a contribution to society this system reduces the number of road accidents occurs due to untrained drivers.